The Problematic Management Of Waqf In Subulussalam (The Overlap Between Law Number 41 Of 2004 And Qanun Aceh Number 10 Of 2018) - Endang Suhendra; Henry Aspan; Bambang Fitrianto (Badan Penerbit STIEPARI Press, 2023)
The Indonesian Waqf Board, abbreviated as BWI, is an independent institution established by the government to implement and develop waqf in Indonesia based on Article 47, paragraph 1 of Law Number 41 of 2004. Aceh is part of Indonesia within the scope of this legislation. However, because Aceh is a unique and autonomous region, Aceh has the authority to form its regulations governing Islamic law, including religious assets as regulated in Law Number 11 of 2006 concerning the Government of Aceh. Religious assets referred to in the law include zakat, infaq ṣadaqah, and waqf for the institution that regulates the management rights is an institution of specialty and specificity in the Government of Aceh and District / Municipal Government which, in carrying out its duties is independently authorized to maintain, maintain, manage and develop zakat, infaq, waqf assets and other religious assets, namely Baitul Mal by Aceh Qanun No. 10 of 2018 concerning Baitul Mal. The existence of two different institutions that manage waqf has resulted in the problematic management of waqf in Aceh and the overlapping rules and authorities of each institution. This research is a normative-empirical research with the category of live-case study based on empirical observations of waqf management according to Law Number 41 of 2004 and Aceh Qanun Number 10 of 2018 to analyze the Law used in the management of Waqf in Subulussalam Aceh. The normative legal research method is focused on analyzing legal documents and applying a library research approach. At the same time, the empirical legal research method requires direct observation, so research activities involve direct observation of waqf management according to Law Number 41 of 2004 and Aceh Qanun Number 10 of 2018.